2000
DOI: 10.1038/82565
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the uncoupling protein-2 gene in mice reveals a role in immunity and reactive oxygen species production

Abstract: The gene Ucp2 is a member of a family of genes found in animals and plants, encoding a protein homologous to the brown fat uncoupling protein Ucp1 (refs 1-3). As Ucp2 is widely expressed in mammalian tissues, uncouples respiration and resides within a region of genetic linkage to obesity, a role in energy dissipation has been proposed. We demonstrate here, however, that mice lacking Ucp2 following targeted gene disruption are not obese and have a normal response to cold exposure or high-fat diet. Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
842
1
11

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 985 publications
(900 citation statements)
references
References 27 publications
43
842
1
11
Order By: Relevance
“…4,7,8 High expression of UCP2 has been reported in cells of the immune system, and the expression was affected by the -866 G variation in vivo and in vitro. 4,9,10 The -866 G allele decreasing the UCP2 expression is associated with increased risk to chronic inflammatory diseases. This observation is consistent with findings in mouse studies, where UCP2-deficient mice were more susceptible to experimental autoimmune encephalomyelitis (EAE) and showed stronger immune responses to infections than wild-type controls.…”
Section: Association Of Ucp2 à866 G/a Polymorphism X Yu Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…4,7,8 High expression of UCP2 has been reported in cells of the immune system, and the expression was affected by the -866 G variation in vivo and in vitro. 4,9,10 The -866 G allele decreasing the UCP2 expression is associated with increased risk to chronic inflammatory diseases. This observation is consistent with findings in mouse studies, where UCP2-deficient mice were more susceptible to experimental autoimmune encephalomyelitis (EAE) and showed stronger immune responses to infections than wild-type controls.…”
Section: Association Of Ucp2 à866 G/a Polymorphism X Yu Et Almentioning
confidence: 99%
“…This observation is consistent with findings in mouse studies, where UCP2-deficient mice were more susceptible to experimental autoimmune encephalomyelitis (EAE) and showed stronger immune responses to infections than wild-type controls. 9,11 As the A allele increasing the gene expression is associated with a decreased risk to diseases, it suggests that the UCP2 protein play a protective role in chronic inflammatory diseases.…”
Section: Association Of Ucp2 à866 G/a Polymorphism X Yu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their similarity of sequence, UCP2 and UCP3 were first suggested to play a role in regulated thermogenesis [2]. Later studies demonstrated that this may not be the case [3] and now evidence is accumulating in favour of a role in reducing the production of reactive oxygen species (ROS) by the mitochondria [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The results from these mice also suggest that UCP2 -3 may be important for the regulation of ROS. The UCP2 null mice seem to produce less ROS than the wild-type mice (Arsenijevic et al, 2000), and the UCP3 null mice have increased production of ROS (Vidal-Puig et al, 2000). Recently, Echtay et al (2002) showed that superoxide activates UCP1 -3 proteins and the uncoupling is induced by fatty acids.…”
Section: Discussionmentioning
confidence: 99%